Seminal characteristics and efficacy of egg yolk free semen extender on cryopreservation of Murrah buffalo bull semen - Jaiswal, Vikash Kumar; Tiwari, Rajendra Prasad; Mishra, Girish Kumar; Bhatt, Pingla; Sahasrabudhe, Sanjeev; Nair, Ajit Kumar (Buffalo Bulletin, 2024)
The experiment was undertaken to study the efficacy of egg yolk free semen extender on cryopreservation of buffalo semen. A total of 24 semen ejaculates from Murrah bulls (5 to 6 years) maintained at Central Semen Station, Anjora, Durg, Chhattisgarh were divided into two aliquots and were diluted using Tris-fructose-egg yolk-glycerol (TFYG) and egg yolk free commercial extender (EYFCE, AndroMed). The overall average Murrah bull fresh semen volume (mL), sperm concentration (million/mL), initial progressive motility (%), live sperm (%), abnormal spermatozoa (%), intact acrosome (%) and HOS reactive sperm (%) were 4.90±0.49, 1286.92±100.23, 75.00±0.67, 81.45±0.61, 10.70±0.51, 80.16±0.43 and 68.83±0.40, respectively. There was significant difference between bulls in semen volume (P<0.01), individual motility (P<0.01) and total sperm abnormalities (P<0.05). The semen extended with TFYG and EYFC extenders were cryopreserved in french mini-straw (0.25 mL) using programmable bio-freezer. The mean values of post thaw motility (%), live sperm (%), abnormal sperm (%), intact acrosome (%), HOST (%) of Murrah bull semen extended with TFYG and EYFCE were 45.83±0.77 vs 49.16±1.33, 57.41±0.54 vs 58.62±0.73, 12.54±0.46 vs 12.45±0.63, 69.62±0.82 vs 71.45±0.64 and 56.45±0.52 vs 57.37±0.55, respectively. Post thaw motility, live spermatozoa and intact acrosome were significantly higher (P<0.01) in frozen thawed semen extended with as EYFCE compared to TFYG in Murrah bull semen. It is concluded that EYFCE results in improvement in post thaw semen characteristics viz. post thaw motility, live sperm percent and intact acrosome.